Hydrogeochemical characteristics and the genesis of the No. Lu 32 well in the Jiaodong Peninsula, China - Du, Guilin; Zhai, Bin; Su, Shujuan; Sui, Lailun; Chang, Xiangchun; Ren, Hongwei; Sun, Maiyu; Wang, Lili (Frontiers in Earth Science, 2023)
The No. Lu 32 well is a seismic observation well situated on the easternmost tip of the Penglai–Weihai fault zone in the Jiaodong Peninsula. It is necessary to reveal the genetic mechanism of the water in this well for earthquake forecasting along the Penglai–Weihai fault zone. Water samples were collected from the No. Lu 32 well, neighboring wells, and seawater to measure the hydrochemical composition and main hydrogen and oxygen isotopic compositions. The water type of the No. Lu 32 well is Cl–Na, which may be due to the influence of seawater intrusion. Hydrogen and oxygen isotopes indicate that the No. Lu 32 well and adjacent wells are mainly influenced by meteoric water, that the high salinity in the water is mainly from the mixing of modern seawater, and that the proportion of seawater there is approximately 5%. Observation of water temperature data in the No. Lu 32 well over several years shows regular annual variations. This comprehensive study shows that the well is greatly affected by seawater backflow infiltration and shallow water. The results of this paper provide an important reference for exploring the hydrogeochemical characteristics and genesis of wells in other coastal zones.